Riding the waves of success: unveiling the sports branding of the ASIAN beach games 2008 Bali - Muhammad Ikbar Ishomi (Institute of Computer Science (IOCS), 2024)
Riding the Waves of Success: Unveiling the Sports Branding of the Asian Beach Games 2008 Bali